Retrospective analysis of the safety of peripherally inserted catheters versus implanted port catheters during first‐line treatment for patients with diffuse large B‐cell lymphoma. (21st March 2022) - Pénichoux, Juliette; Rio, Julien; Kammoun, Leila; Vermeulin, Thomas; Pepin, Louis‐Ferdinand; Camus, Vincent; Dubois, Sydney; Bouclet, Florian; Alani, Mustafa; Contentin, Nathalie; Leprêtre, Stéphane; Stamatoullas, Aspasia; et al.
Abstract: Objectives: Both peripherally inserted central catheters (PICCs) and implanted port catheters (PORTs) are commonly used for the delivery of immunochemotherapy. We compared the safety of the two types of devices in a homogeneous and monocentric population of diffuse large B‐cell lymphoma (DLBCL) patients who were treated with first‐line immunochemotherapy by evaluating the numbers of catheter‐related venous thromboses (VTs) and infections that occurred in the six months after implantation according to the type of device. Methods: Using a propensity score, the adjusted relative risk (ARR) between the type of catheter and the occurrence of catheter‐related complications (infection and/or VT) of interest was retrospectively determined. Results: 479 patients were enrolled (266 PORTs/213 PICCs), and 26 VTs (5.4%) and 30 infections (6.3%) were identified in the period following PICC/PORT implantation. The adjusted relative risk (ARR) of catheter‐related complications (infection and/or VT) according to the type of device was 2.6 (95% CI =1.3–5.9, p  = .0075). This risk increase associated with the PICC device was significant for both infections (ARR = 3.2; 95% CI = 1.3–10.9) and thrombosis (ARR = 4; 95% CI = 1.5–11.6). Conclusion: Our study supports the preferential use of PORTs for the first line of treatment for DLBCL patients.